Pertimbangan Hakim dalam Menjatuhkan Pidana terhadap Terdakwa yang Berstatus Sebagai Justice Collaborator dalam Tindak Pidana Korupsi Kasus Suap Penghapusan Red Notice Djoko Tjandra - Nufus Hidayah; Ade Mahmud (Bandung Conference Series: Law Studies, 2022)
Abstract. Justice Collaborator has a very important role in uncovering cases of corruption although in practice there are often problems such as protection issues, reward, mechanisms for applying for protection and determination of Justice Collaborator status. Research aims to find out how the rights and obligations of defendants who are Justice Collaborators in the Bribery Case Of Red Notice Removal Djoko Tjandra according to Indonesia's positive law; and how the judge's consideration in sentencing criminals against defendants who are Justice Collaborators in the bribery case of djoko tjandra red notice removal. Research uses a normative juridical approach, with research specifications in the form of descriptive analytical, research stages conducted with literature studies, and to analyze data using qualitative normative methods. The results showed that the determination of the status of justice collaborator against the defendant in the bribery case of djoko tjandra red notice removal raises juridical implications for the accused, namely in the form of rights obtained as stipulated in Article 6 paragraph (1) of the Joint Regulation, namely: Physical and psychological protection; Legal protection; Special handling; And awards. In addition to rights, a Justice Collaborator also has an obligation including by providing information and evidence that is very significant so that investigators and / or public prosecutors can uncover the criminal act effectively, uncover other perpetrators who have a greater role and / or return the assets / results of a criminal act. Regarding the judge's consideration in case Number: 48/Pid.Sus-Tpk/2020/PN.Jkt.Pst, the status of Justice Collaborator was considered even though Tommy Sumardi was a defendant. Even so, the sentence of imprisonment and criminal fines by the Panel of Judges against Defendant Tommy is higher than the prosecutor's demands, this indicates that criminal conviction by the judge has not rested on the spirit of appreciation for a Justice Collaborator for his services in uncovering a criminal case. Abstrak. Justice Collaborator memiliki peran yang sangat penting dalam mengungkap kasus tindak pidana korupsi meskipun dalam praktinya seringkali terjadi masalah seperti masalah perlindungan, pemberian penghargan, mekanisme mengajukan perlindungan dan penetapan status Justice Collaborator. Penelitian bertujuan untuk mengetahui bagaimana hak dan kewajiban terdakwa yang berstatus Justice Collaborator dalam Kasus Suap Penghapusan Red Notice Djoko Tjandra menurut hukum positif Indonesia; dan bagaimana pertimbangan hakim dalam menjatuhkan pidana terhadap terdakwa yang berstatus Justice Collaborator dalam kasus suap penghapusan red notice Djoko Tjandra. Penelitian menggunakan pendekatan yuridis normatif, dengan spesifikasi penelitian berupa deskriptif analitis, tahap penelitian dilakukan dengan studi kepustakaan, dan untuk menganalisis data menggunakan metode normatif kualitatif. Hasil penelitian menunjukan bahwa Penetapan status justice collaborator terhadap terdakwa dalam kasus suap penghapusan red notice Djoko Tjandra menimbulkan implikasi yuridis bagi terdakwa, yaitu berupa hak-hak yang diperoleh sebagaimana diatur dalam Pasal 6 ayat (1) Peraturan Bersama, yakni berupa : Perlindungan fisik dan psikis; Perlindungan hukum; Penanganan secara khusus; dan Penghargaan. Selain hak, seorang Justice Collaborator juga memiliki kewajiban diantaranya dengan memberikan keterangan dan bukti-bukti yang sangat signifikan sehingga penyidik dan/atau penuntut umum dapat mengungkap tindak pidana dimaksud secara efektif, mengungkap pelaku-pelaku lainnya yang memiliki peran lebih besar dan/atau mengembalikan aset-aset/hasil suatu tindak pidana. Mengenai pertimbangan hakim dalam perkara Nomor : 48/Pid.Sus-Tpk/2020/PN.Jkt.Pst, status Justice Collaborator dipertimbangkan sekalipun Tommy Sumardi merupakan terdakwa. Meski begitu, penjatuhan pidana penjara dan pidana denda oleh Majelis Hakim terhadap Terdakwa Tommy lebih tinggi daripada tuntutan Jaksa, hal ini mengindikasikan bahwa penjatuhan pidana oleh hakim belum bersandar pada semangat penghargaan bagi seorang Justice Collaborator atas jasanya dalam mengungkap suatu perkara pidana.